Análisis comparativo de los contenidos comunicacionales de los medios digitales de la Provincia de Los Ríos - Bajaña Chávez, Jelitza Julady (2025)
The general objective of this study is to carry out a comparative the general objective of this study is to carry out a comparative analysis of the communicational contents of the digital media in the province of Los Ríos, with the digital media in the province of Los Ríos, in order to identify the characteristics and trends in the dissemination of information characteristics and trends in the dissemination of information. To achieve this a mixed approach methodology is used, combining quantitative and qualitative elements quantitative and qualitative elements. A non-experimental design is used, where the frequency of and the frequency of publication and the scope of the contents, as well as the narratives and communicative styles, as well as the narratives and communicational styles of the local media. The study population includes various digital media, and measurement techniques and instruments are applied to ensure the measurement instruments are applied to ensure the validity of the data collected. The conclusions of the study indicate that the digital media in the Province of Los Ríos present. Los Ríos present significant variations in their communication approaches, which reflects differences in the coverage of issues and in the interaction with the audience the audience. In addition, it highlights the importance of transparency and objectivity in research, ensuring and objectivity in the research, ensuring that the results are presented in a clear and honest manner in a clear and honest manner. This analysis not only contributes to the understanding of digital media in the region, but also offers recommendations to improve the quality of the information disseminated.